Entrepreneurship Perception of Sports Management Students: Social and Cultural Factors - Çiftçi, İsa; Tan, Çetin (Akan BAYRAKDAR, 2025)
This study aims to examine the relationship between individual entrepreneurship perception levels and the characteristics of social and cultural capital among undergraduate students studying Sports Management within the field of sports sciences.The research population consisted of 2,288 students enrolled in Sports Management departments across the Eastern Anatolia Region of Turkey. A total of 1,622 students were selected as the sample using a stratified sampling method. Data were collected through the Personal Information Form, the Individual Entrepreneurship Perception Scale (IEPS), and the Social and Cultural Capital Characteristics Questionnaire (SCCQ).The findings revealed no statistically significant relationship between individual entrepreneurship perception and social capital (r = .010, p = .685) or cultural capital (r = .015, p = .551) when analyzed separately. However, the multiple regression analysis showed that social capital had a statistically significant effect on individual entrepreneurship perception when combined with cultural capital (? = .076, p = .045). Furthermore, strong positive correlations were observed between cultural capital and specific sub-dimensions of entrepreneurship perception, including planning (r = .783, p < .001), communication (r = .838, p < .001), motivation (r = .838, p < .001), and self-discipline (r = .738, p < .001). The results suggest that while social and cultural capital may not independently predict entrepreneurship perception, their combined influence plays a significant role. Accordingly, educational programs and extracurricular activities aimed at enhancing students' social and cultural capital are essential for fostering entrepreneurial potential among sports management students.
Keywords: Sports Activity Management; Spor Faaliyetleri Yönetimi